2017
DOI: 10.1515/freq-2016-0288
|View full text |Cite
|
Sign up to set email alerts
|

Design of High Performance Microstrip LPF with Analytical Transfer Function

Abstract: By exploiting butterfly and T-shaped resonators, a new design of microstrip lowpass filter (LPF) is proposed and analyzed. The LPF is investigated in four sections. Analyzing initial resonator and its equation in detail, providing a sharp skirt by using series configuration, suppressing in middle frequencies and suppressing in high frequencies are focused in each section, respectively. To present a theoretical design, LC equivalent circuit and transfer function are precisely calculated. The measured insertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…From Table 6, it can be clearly observed that the suggested LPF is superior to the previously published LPFs. The parameters in Table 6 are comprehensively explained and mentioned in References 12 and 24…”
Section: Measurement Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From Table 6, it can be clearly observed that the suggested LPF is superior to the previously published LPFs. The parameters in Table 6 are comprehensively explained and mentioned in References 12 and 24…”
Section: Measurement Results and Discussionmentioning
confidence: 99%
“…LPFs play a key role in wireless communication systems owing to their tasks in eliminating unwanted harmonics and noise 3 . Growing demands for these elements motivate scientists to design LPFs with diverse structures and specifications 4‐19 . C‐shaped structures along with complementary split‐ring resonators were used to design an LPF 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compact size, negligible losses (insertion and return loss), high roll‐off rate and wide stopband are considered as the most efficient factors in LPFs designing. Numerous structures of LPFs have been proposed and analyzed in order to enhance these features . Using hairpin resonators and rhombic stubs, two LPFs were suggested in Refs., respectively, but both of them suffer from gradual transition bands.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve a narrower transition band, butterfly resonators were employed in Ref. . Despite reaching high selectivity, the stopband bandwidth of the designed LPF in Ref.…”
Section: Introductionmentioning
confidence: 99%